Remuneração variável como estratégia de desempenho: um estudo de caso de varejo especializado - Esotico, João Oswaldo (2017)
The objective of the present study was to examine how a strategic remuneration system, linked to a set of objectives, goals, indicators and initiatives that express the strategic uniqueness of an Organization and that can contribute to reach strategic implementations. For this verification, we conducted a case study with the retail trade company RaiaDrogasil, seeking to know if there is a relationship between its strategy - organic growth - and the systematic variable remuneration adopted at various levels of the organization. In order to verify this relationship, an analysis was made with the historical data of the company, in November / 2011, when the Raia and Drogasil drugstores were merged, both publicly traded, by 2015, comparing its physical expansion and increase of the company's value with the Shares traded on the stock exchange, as well as the various Remuneration models adopted for each area of the company, and levels of organizational command. The theoretical basis of the work is presented in two separate strands, one regarding the Strategy and its Implementation, and the other reasoning regarding the Strategic Remuneration, focused mainly on Variable Remuneration. It is verified that the study shows a relativity between the elaboration of the strategy and its implementation with participation of the variable remuneration in the achievement of the established goals